Evaluation of Peppermint Based Menthol as a Cooling Agent for Development of Hydrogel Cooling Patch - bin Hasnadi, Mohamad Syahir; A Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2022)
Peppermint as a cooling agent helps to give cooling and fresh sensation and specific sensory toward human’s skin. A cooling agent also has the potential to help tone down the heat from someone with a fever. It is related to menthol that gives the cooling sensation. Menthol is derived from peppermint because it has a high menthol content. In this project, the combination of hydrogel which consists of polyvinyl alcohol, hydroxypropyl methylcellulose, polyethene glycol and peppermint oil were used for the formulation of the hydrogel cooling patch. The extraction of menthol from peppermint was using the Soxhlet extraction process towards 1000g of dried peppermint leaves to produce peppermint oil. The formulation of hydrogel was evaluated for its adhesiveness property via the lap shear test and its cooling sensation property via the sensory evaluation test. Sample 6 has a good adhesive property and it was very easy to apply the patch to apply on skin. The cooling sensation also was good and the sample scored a high mark during the sensory evaluation test. In conclusion, the hydrogel formulation of sample 6 gives the best result as a cooling patch.